2022
DOI: 10.1371/journal.pone.0272798
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of high-oleic rapeseed (Brassica napus) based on quality, resistance, and yield traits: A new method for rapid identification of high-oleic acid rapeseed germplasm

Abstract: To scientifically evaluate and utilize high-oleic acid rape germplasm resources and cultivate new varieties suitable for planting in the Hunan Province, 30 local high-oleic acid rape germplasms from Hunan were used as materials. The 12 personality indices of quality, yield, and resistance were comprehensively evaluated by variability, correlation, principal component, and cluster analyses. The results of variability showed that except for oleic acid, the lowest coefficient of variation was oil content, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In PCA including enzymatic and agronomic data, yield, harvest index (HI) and seed oil content clustered together and were negatively correlated with dry matter biomass formation, height, onset of flowering and seed protein content. These correlations are in line with that of other crops including Brassica napus (Chang et al, 2022;Marjanović-Jeromela et al, 2011;Stolte et al, 2022) and the negative correlation between seed oil content and seed protein content reported for camelina (Vollmann et al, 2005). It is worth noting that the correlations observed were not only evident in developing seeds but also in leaves, underpinning that physiological process throughout development influence agronomic characters.…”
Section: Discussionsupporting
confidence: 86%
“…In PCA including enzymatic and agronomic data, yield, harvest index (HI) and seed oil content clustered together and were negatively correlated with dry matter biomass formation, height, onset of flowering and seed protein content. These correlations are in line with that of other crops including Brassica napus (Chang et al, 2022;Marjanović-Jeromela et al, 2011;Stolte et al, 2022) and the negative correlation between seed oil content and seed protein content reported for camelina (Vollmann et al, 2005). It is worth noting that the correlations observed were not only evident in developing seeds but also in leaves, underpinning that physiological process throughout development influence agronomic characters.…”
Section: Discussionsupporting
confidence: 86%
“…This study not only provides a new method for the early screening of oleic acid in rapeseed but also provides the basis for the early screening of other quality traits in rapeseed. The previous research of our team showed that the oleic acid content of rapeseed is variously related to the quality of protein, erucic acid, and others [22]. In addition, part of spectral information in the rape seedling stage is sensitive to oil content and yield [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis can categorise genetically similar germplasm into a single group, thereby elucidating taxonomic characteristics and relationships [35]. At a Euclidean distance of 17 (as illustrated in Figure 3), 192 maize accessions can be categorized into three principal groups, as detailed in Tables 4 and 5.…”
Section: Cluster Analysis Of Maize Accessionsmentioning
confidence: 99%